2008
DOI: 10.1158/1535-7163.mct-08-0507
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal antiestrogen-binding site ligands induce growth control and differentiation of human breast cancer cells through the modulation of cholesterol metabolism

Abstract: The microsomal antiestrogen-binding site (AEBS) is a highaffinity membranous binding site for the antitumor drug tamoxifen that selectively binds diphenylmethane derivatives of tamoxifen such as PBPE and mediates their antiproliferative properties. The AEBS is a hetero-oligomeric complex consisting of 3B-hydroxysterol-# 8 -# 7 -isomerase and 3B-hydroxysterol-# 7 -reductase. High-affinity AEBS ligands inhibit these enzymes leading to the massive intracellular accumulation of zymostenol or 7-dehydrocholesterol (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 43 publications
1
87
0
Order By: Relevance
“…We recently established that AEBS ligands induce differentiation and apoptosis in breast cancer cells through a mechanism involving the production of sterol autoxidation products, and that vitamin E inhibits these effects (3,4,12). Consistent with these data, previous reports have shown a limited clinical outcome with Tam treatment when cholesterol metabolism enzymes (28) or antioxidant enzymes (29) are overexpressed in breast tumors.…”
Section: D8d7i and Dhcr7 Coexpression Allows The Reconstitution Of Chehmentioning
confidence: 55%
See 3 more Smart Citations
“…We recently established that AEBS ligands induce differentiation and apoptosis in breast cancer cells through a mechanism involving the production of sterol autoxidation products, and that vitamin E inhibits these effects (3,4,12). Consistent with these data, previous reports have shown a limited clinical outcome with Tam treatment when cholesterol metabolism enzymes (28) or antioxidant enzymes (29) are overexpressed in breast tumors.…”
Section: D8d7i and Dhcr7 Coexpression Allows The Reconstitution Of Chehmentioning
confidence: 55%
“…ChEH is the last member of the epoxide hydrolase family with an unidentified coding gene. The results from these studies, along with the relationship that we established between sterol autoxidation products and the functions of the AEBS (3,4,12), suggested to us a pharmacological and structural link between the AEBS and ChEH, which we investigated in the present study. Our results indicate that the enzymes that form the AEBS are involved in the catalytic activity of ChEH.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…As compared to our previous results 7 , the sterol composition in gonads of N. concinna and N. fuscoviridis was Interestingly, the resumption of meiosis in an in vitro maturation and fertilization mouse model has been reported to be induced by zymosterol. Recently, it has been reported that zymostenol inhibits cell growth 18 , whereas desmosterol was shown to stimulate cell proliferation and survival 19 .…”
Section: Resultsmentioning
confidence: 99%